Study on relationship between stroke and kidney dysfunction based on estimated glomerular filtration rate (eGFR) - Jahan, Sharmin; Begum, Rokeya; Akhter, Qazi Shamima (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: Stroke is one of the commonest causes of severe disability and accounts for a large proportion of health care resources. Kidney diseases are related to stroke and reduced estimated glomerular filtration rate (eGFR) appears to be a significant independent prognostic factor for short as well as long term mortality in stroke patients. Objective: The present study has been designed to assess the relationship between stroke and kidney dysfunction based on eGFR. Methods: The present study was a case control study. The study was conducted in the Department of Physiology, Dhaka Medical College and Hospital (DMCH), Dhaka from 1st July 2010 to 30th June 2011. A total of 200 subjects were included with the age limit of 3585 years. Out of them 100 apparently healthy subjects were selected as control(Group A) for comparison and 100 diagnosed stroke patients were selected as study group (Group B). On the basis of age, group A and group B were further subdivided into group A1(age 35-59 years) consisting of 47 normal persons and group A2(age 60-85 years) consisting of 53 normal person, group B1(age35-59 years) was consisting of 42 stroke patients and group B2(60-85 years) consisting of 58 stroke patients .The study subjects were selected from admitted patients in Department of Medicine, DMCH, Dhaka. Estimated GFR (eGFR) were measured by MDRD equation. The data was analyzed by computer based statistical software (SPSS version 12). Results: The result was expressed as Mean (+SD). The test of significance was calculated and p values <0.05 was accepted as level of significance. The mean(±SD)of eGFR level was significantly(p<0.001) lower in group B1 and B2 than that of group A1 and A2 respectively. Conclusion: From this study it can be concluded that, stroke patients suffers from kidney dysfunction than that of normal control group on the basis of measuring eGFR. http://dx.doi.org/10.3329/bjpp.v29i1-2.20062 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 12-16